The Role of Credit Access in Firm Sustainability: A Comparison of the 1998 and 2003 Surveys of Small Business Finances - Mach, Traci L. (Senate Hall, 2014)
The current paper uses two nationally representative cross-sections of US businesses from 1998 and 2003 to examine 5-year survival rates of small businesses. Despite the fact that the 2003 cohort experienced the Great Recession at the end of their 5-year window, exits were about 4 percent higher for the 1998 cohort than the 2003. The analysis finds that credit access and credit quality measures are among the most important explanatory variables in each period. Using the Blinder-Oaxaca decomposition to decompose the differences across the cohorts, the data further indicate that the lower survival rate in the 1998 cohort is largely driven by differences in the coefficients on the credit access and credit quality measures. On the other hand, measures of real estate appreciation and depreciation do not seem to have played a large role in the difference. Keywords: Small businesses finances, firm discontinuance, SSBF, NETS
Keywords: small businesses finances|firm discontinuance|SSBF|NETS